Planning As Magma. Suggestions From The Work Of Cornelius Castoriadis - Triantis, Loukas (AESOP, 2024)
The philosophical work of Cornelius Castoriadis on the imaginary institution of society can inform planning theory today at a juncture of major transitions, unprecedented global urbanisation, multiple crises, and conflict. Planning as magma constitutes a dynamic world of social imaginary significations, which goes beyond plans, legal frameworks, administrative processes, and professional practices. This highlights the political dimensions of planning as thinking and doing interwoven with consensual or conflictual social dynamics, representations, desires, finalities, and affects. Derivative values such as indetermination, infinite potentiality, inexhaustibility, multiplicity, and difference may open paths to self-reflection, selftransformation, and radical imagination. Planning as magma means to elucidate planning goals and orientations, to conceive new social imaginary significations, and to constitute new methodologies, epistemologies, policies, and practices, toward sustainability and justice. Keywords: planning theory; spatial planning; philosophy; magma; Cornelius Castoriadis
Game changer? Planning for just and sustainable urban regions, Paris, 8-12th July 2024